Formation of approach to research of economic reliability of intellectual infrastructure of technological development of industrial enterprises - E. V. Yakovleva; A. R. Terentyeva (Омский научный вестник: Серия "Общество. История. Современность")
One way to ensure the economic reliability of industrial enterprises in modern conditions of digitalization of the economy is to form mechanisms of economic reliability of intellectual infrastructure of technological development of industrial enterprises, which are adequate to these conditions. The work presents the results of the study aimed at justifying and choosing a methodological approach to the formation of mechanisms of economic reliability of the intellectual infrastructure of technological development of industrial enterprises subject to digital transformation of business processes, which causes theoretical significance and novelty of the results obtained. The methodological basis of the study is the popular scientific methods of classification, generalization, comparison, analysis